Career Adaptability, Perceived Overqualification, and The Turnover Dilemma - Wibowo, Winastanto; Suhariadi, Fendy; Dinda Nadia, Fiona Niska (Universitas Prasetiya Mulya, 2024)
This study examines the role of perceived overqualification as a mediator in the relationship between career adaptability and turnover intention among employees of PT. Kimia Farma Diagnostika. Involving 80 respondents, this study uses a quantitative approach and SEM-PLS analysis. The results show that career adaptability has a positive effect on turnover intention, where perceived overqualification functions as a mediator. Employees who feel they have higher abilities than needed tend to seek opportunities that are more in line with their potential, which increases the intention to leave the organization. These findings provide important insights for management in designing more effective employee retention strategies, as well as enrich the literature by combining these concepts. By understanding the factors that influence employees' decisions to stay or move, management can develop policies that increase job satisfaction and reduce turnover rates. This study also identifies limitations, such as the limited number of respondents, and suggests further research.